Bedwetting - Garret D. Evans; Heidi Liss Radunovich (EDIS)
Revised! FCS-2112, a 5-page fact sheet by Garret D. Evans Psy.D. and Heidi Liss Radunovich, Ph.D., addresses this common problem affecting about 10% of school-age children. The authors describe the types of enuresis, what constitutes "problem" bedwetting, and what parents should do, including treatment strategies. This version is updated throughout to reflect current research. Published by the UF Department of Family Youth and Community Sciences, August, 2006.